The directory 2000 of the Archdiocese of Manila. - Catholic Church. Archdiocese of Manila. Archdiocesan Office for Research and Development (Manila AORD, 2000)
It contains data based on the official communications and other documents (appointment papers, circulars, etc.) gathered and submitted to the Archdiocesan Office for Research and Development (AORD) on or before December 15, 1999.
Keywords: Dioceses -- Philippines -- Manila Metropolitan Area -- Directories